UPAYA MENINGKATKAN HASIL BELAJAR SISWA DALAM MEMAHAMI NILAI PANCASILA MELALUI PEMBELAJARAN BERDIFERENSIASI DENGAN PENDEKATAN CRT DI KELAS IV SD NEGERI 124 PALEMBANG - Srimulia Purnama; Wulandari Octaviani; Sari Yani; Suci Aminah; Rantika Mayang Sari; Vianti Anatasya; Rukiyah; Dinna Lestari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
In the Pancasila Education class for fourth grade at SD Negeri 124 Palembang for the 2024/2025 academic year, there is an issue with the low learning outcomes of students regarding the material of Pancasila as a Life Value. During the learning process, students are less active and focused. Therefore, a classroom action research (CAR) was conducted using quantitative methods to address this issue. This research aims to improve the learning outcomes of fourth-grade students on the material of Pancasila as a Life Value through differentiated instruction with a Culturally Responsive Teaching (CRT) approach. There was an improvement in student learning outcomes after implementing three cycles. In cycle 1, the percentage of student learning outcomes reached 32%, which did not meet the mastery criteria. In cycle 2, the percentage of learning outcomes reached 63%, still not meeting the success criteria. In cycle 3, the percentage of learning outcomes reached 89%, which met the success criteria. The results show a progressive improvement in each cycle, demonstrating that differentiated instruction with the CRT approach can enhance student learning outcomes.